Developing a Minecraft Adventure Map to Support Eleventh Grade Senior High School Students’ Vocabulary Learning - Eka Bilanti; Endang Susilawati; Luwandi Suhartono; Urai Salam; Yanti Sri Rezeki (Institut Agama Islam Negeri Palopo, 2022)
With the rapid development of technology, Indonesia’s Curriculum demands full support of technology in its implementation. As a result, its incorporation into English language teaching and learning becomes inevitable. One of the ways to incorporate technology in education is by using video games. Thus, this study aimed to develop a Minecraft adventure map as a learning media to support eleventh grade senior high school students’ vocabulary learning. To achieve the aim, this research was done by focusing to know how the product was developed, how it looked like, how appropriate the product was, and what the students’ opinions were towards the product. Therefore, the development research with the model of ADDIE by Branch (2009) was used. The research procedures consisted of analyze, design, and develop stages. The participants of this research were the English teachers of eleventh grade in SMA N 1 Pontianak, and the students of XI MIPA II as selected through purposive sampling. The techniques of data collection involved interviews for analyze stage, a questionnaire for internal evaluation, and another questionnaire to know the students’ opinions of the product. The product was made using Minecraft Java Edition version 1.18.2. It was in the form of a Minecraft adventure map that covered relevant topics of English for eleventh grade students. It was also available for PC and mobile devices. To sum up, it was found that the product was strongly appropriate for the target users through internal evaluation. Moreover, the product received positive responses from most of the targets.